Synthesis and characterization of Fe3O4/SiO2/C nanocomposites and their potential for NH4+ ion removal from shrimp farm wastewater - Syah, Alif Alfarisyi; Syavika, Lukluatus; Wijaya, Anugrah Ricky; Kusumawati, Nita (Eclética Química, 2026)
The synthesized Fe3O4/SiO2/C nanocomposites are adsorbents for NH4+ ion removal from shrimp farm effluent. Fe3O4 nanomagnets were synthesized via coprecipitation, coated with silica and carbon using 2% NaOH activation, and PEG4000 as a binder. Structural characteristics were investigated through XRD, FT-IR, and VSM. Physico-chemical parameters, including adsorbent amount (0.05–0.3 g), contact time (10–70 min), and initial NH4Cl concentration (0.1–0.8 mg L–1), were investigated. Maximum NH4+ removal efficiency (83.5%) was achieved at 55 min with 0.2 g adsorbent mass, using a solution of 0.4 mg L–1 NH4Cl at pH 7 and 25 ºC. Pseudo-second-order kinetic model (R² = 0.9998) was satisfied with an adsorption capacity of 0.037 mg g–1. Langmuir isotherm estimated a capacity range of 0.005 to 0.087 mg g–1. The adsorption process occurs exothermically, spontaneously, and is physisorption. Filtrate analysis by UV-Vis with phenate reagents showed notable reduction in NH4+ levels post-adsorption (0.077-0.282 mg L–1) with GIS visualization, showcasing effective environmental preservation. These nanocomposites successfully adsorbed NH4+ in shrimp pond effluent with potential magnetic recovery.